The Correlation Between Level of Knowledge on Immunological Materials With Healthy Life Style Awareness of Pre-service Biology Teachers - Iseu Laelasari; Izfina Maliyya (Bioeducation Journal, 2022)
The study aims to analyze the relationship between level of knowledge on immunological materials with healthy lifestyle awareness of pre-service biology teachers. Researchers have used correlational research design with a sample of pre-service biology teacher as many as 30 randomly chosen. The instruments developed in this study of 20 multiple choice involving sub-matter of immunological system and 20 online-questionnaire distributed through survey heart app to reveal the healthy lifestyle awareness of participants. Data analysis uses statistical method of Pearson product moment and simply regression after a prerequisite test of normality, linearity and heteroscedasticity test. The results of this study reveal that coefficient correlation of the amount (0.428) means that there is a strong enough correlation between two variables, significant tests show a value of sig 0.018 <0.05. Regression tests show 0.184 determinative coefficient which means that the level of knowledge on immunological material affect to healthy lifestyle awareness by18.4%. The result provides educational implications that it will require integration of healthy lifestyle awareness as part of a character that needs to be strengthened in biology aside.